PENGGUNAAN TEAMS GAMES TOURNAMENT (TGT) DENGAN MEDIA KARTU DALAM MENINGKATKAN HASIL BELAJAR - Wahyu Bagja Sulfemi (JOURNAL OF KOMODO SCIENCE EDUCATION, 2018)
This study aims to improve students' learning outcomes Class IV SDN Pondokcina 5 by using Tames Games Tournament (TGT) model and card media. The method of this research is Classroom Action Research (PTK) which is carried out in Pondokcina State Elementary School 5 Depok City which amounts to 29, consist of 13 men and 16 women. The result of Social Science lesson in pre-cycles with Minimum Exhaustiveness Criterion 75 obtained mean 66. Which complete in learning amount to 12 or 41,4% and that can answer only 5 or 17,2%. While those who can not answer there are 24 or 82.8%. In cycle one result of mean 70,3 which complete study 44,8% or 13 students while observation result which can answer 11 people or 37,9% who do not answer as much as 18 or 62,1%. In cycle two the average value of 78.3 which is complete in learning as much as 23 or 79.3%. While the observation results obtained 89.7% who can answer, learning using Tames Games Tournament model with the card media can improve learning outcomes, motivate activeness for learners so that the material presented by the teacher can be understood, and the responsibility of the learner to the task is high enough.